Analisis Implementasi Underwriting dalam Proses Klaim Asuransi Jiwa Syariah pada PT. AJS Bumiputera KPS. Medan - Anjani Rizky Amelia; Rahmi Syahriza (Universitas Muhammadiyah Surabaya, 2022)
This study aims to understand how the implementation of underwriting in the claim process on sharia life insurance at PT. AJS Bumiputera KPS. Medan and to understand what factors underwriters can consider in the underwriting process in the claims process at PT. AJS Bumiputera KPS. Medan. The type of research used is descriptive qualitative research. The results of the study show that in general there are four claims processes including notification of claims, proof of claim documents, investigation of claims and settlement of claims. Claims investigation is carried out if at the time of verification, irrelevant data is found. The cause of the delayed claim is the lack of documents provided by the institution on behalf of the participants to the insurance so that the claim is postponed until the file is completed at the specified time. The cause of the rejected claim is the policy status is not active, the participant is not a member, violates the principle of